Evidence From a Multistate Cohort: Enrollment in Affordable Care Act Qualified Health Plans’ Association With Viral Suppression - McManus, Kathleen A (Clin Infect Dis, 2019)
BACKGROUND: Healthcare delivery changes associated with viral suppression (VS) could contribute to the United States’ “Ending the HIV Epidemic” (EtHE) initiative. This study aims to determine whether Qualified Health Plans (QHPs) purchased by AIDS Drug Assistance Programs (ADAPs) are associated with VS for low-income people living with HIV (PLWH) across 3 states. METHODS: A multistate cohort of ADAP clients eligible for ADAP-funded QHPs were studied (2014–2015). A log-binomial model was used to estimate the association of demographics and healthcare delivery factors with QHP enrollment prevalence and 1-year risk of VS. A number needed to treat/enroll (NNT) for 1 additional person to achieve viral suppression was calculated. RESULTS: Of the cohort (n = 7776), 52% enrolled in QHPs. QHP enrollment in 2015 was associated with QHP coverage in 2014 (adjusted PR [aPR], 3.28; 95% confidence intervals [CIs], 3.06–3.53) and engagement in care in 2014 (aPR, 1.16; 1.04–1.28). PLWH who were engaged in care (n = 4597) and had QHPs had a higher VS rate than those who received medications from Direct ADAP (86.0% vs 80.2%). QHPs’ NNT for an additional person to achieve VS is 20 (14.1–34.5). Starting undetectable (adjusted risk ratio [aRR], 1.39; 1.28–1.52) and enrolling in QHPs in 2015 (aRR, 1.06; 0.99–1.14) was associated with VS. CONCLUSIONS: Once enrolled in ADAP-funded QHPs, ADAP clients stay enrolled. Enrollment is associated with VS across states/demographic groups. ADAPs, especially in the South and in Medicaid nonexpansion states, should consider investing in QHPs because increased enrollment could improve VS rates. This evidence-based intervention could be part of EtHE.